2008
DOI: 10.5694/j.1326-5377.2008.tb01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower than expected morbidity and mortality for an Australian Aboriginal population: 10‐year follow‐up in a decentralised community

Abstract: Objective: To examine mortality from all causes and from cardiovascular disease (CVD), and CVD hospitalisation rate for a decentralised Aboriginal community in the Northern Territory. Design and participants: For a community‐based cohort of 296 people aged 15 years or older screened in 1995, we reviewed hospital and primary health care records and death certificates for the period up to December 2004 (2800 person‐years of follow‐up). Main outcome measures: Mortality from all causes and CVD, and hospitalisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 12 publications
(16 reference statements)
3
73
0
Order By: Relevance
“…A recent study by Burgess et al [26] showed that caring for country was associated with significantly more frequent physical activity, better diet, lower body mass index, less abdominal obesity, lower systolic blood pressure, less diabetes, non-elevated albumin-creatinine ratio, higher high density cholesterol lipoprotein cholesterol level, lower cardiovascular risk and reduced mortality in Indigenous Australians. In a recent study by Rowley et al [27], lower than expected cardiovascular morbidity and all-cause mortality in a decentralized Aboriginal community in the Northern Territory were attributed to regular primary health care services, better physical activity and diet, limited access to alcohol, social factors and self-determination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Burgess et al [26] showed that caring for country was associated with significantly more frequent physical activity, better diet, lower body mass index, less abdominal obesity, lower systolic blood pressure, less diabetes, non-elevated albumin-creatinine ratio, higher high density cholesterol lipoprotein cholesterol level, lower cardiovascular risk and reduced mortality in Indigenous Australians. In a recent study by Rowley et al [27], lower than expected cardiovascular morbidity and all-cause mortality in a decentralized Aboriginal community in the Northern Territory were attributed to regular primary health care services, better physical activity and diet, limited access to alcohol, social factors and self-determination.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted remoteness contributes to variable access to health care and is an independent predictor for poorer health outcomes [5, 6, 7, 31, 32]. Despite these significant gaps there is evidence to show that we are capable of making inroads, but this requires common sense and getting’s some basics right [33]. The bigger question is whether we can sustain such efforts for long periods, given the transitional nature of scientific funding and political sentiment.…”
Section: Disparities In Heart Failure Outcomesmentioning
confidence: 99%
“…A defining summary on traditional Indigenous views on health has been provided by Maher and is sufficiently authoritative to ensure it is essential reading for any medical context [35]. Similarly health system perspectives on Indigenous health have been summarised [14, 33-49]. What is lacking is direct information from the Indigenous clients themselves.…”
Section: Does Traditional Indigenous Life-styles Represent An Impedimmentioning
confidence: 99%
“…A Healthy Lifestyles project in north-east Arnhemland also included a family food garden program that involved staff working with families to establish backyard gardens, a community market which allowed access to fresh fruits, bush foods, fish and shell-fish, and a policy of not selling deep-fried takeaway foods until at least 11 am [16]. In an evaluation of the effects of returning to traditional Country away from an urban environment, major benefits of the associated changes in diet and lifestyle on diabetes control were identified [21] and similar benefits are likely to have accrued from other programs that included Homelands living [37,41]. In an attempt to divert spending away from tobacco and alcohol to healthier dietary choices, income management for all Aboriginal people on social security payments was made mandatory under the Northern Territory Emergency Response [43], This required change at the Federal Government level by suspending the Racial Discrimination Act 1975 to allow its implementation [51].…”
Section: Resultsmentioning
confidence: 99%